The Impact of Chinese EFL Teachers’ Emotion Regulation and Resilience on Their Success - Li, Ling; Lv, Lili (Frontiers in Psychology, 2022)
Succeess in EFL/ESL contexts by teachers requires developing some essential characteristics consisting of several interacting variables and underlying constructs. With the rise of positive psychology, the concepts of resilience and emotion regulation and their roles in the EFL/ESL milieu have caught attention. In this line, the present study aims to investigate whether there would be any relationship among EFL teachers’ resilience, emotion regulation, and their success in the Chinese context. In addition, we tried to examine the predictive power of EFL teachers’ resilience and emotion regulation toward their success. To that end, an online Likert scale questionnaire including items on teachers’ emotion regulation, teachers’ resilience, and teaching success was distributed to 323 Chinese EFL teachers. The participants were selected based on convenience sampling. Spearman Rho correlation index and multiple regression analysis along with ANOVA were used to analyze the collected data. The findings showed a direct and positive correlation among EFL teachers’ emotion regulation, resilience, and success. Furthermore, it was indicated that EFL teachers’ resilience was more powerful in terms of predicting success than their emotion regulation. Our findings imply that teacher education programs can enhance EFL teachers’ success through training resilience strategies and emotion regulation skills.